Accumulation of 99mTc-Glutathione in Head and Neck Tumors - Ercan, M. T.; Aras, T.; Aktaş, A.; Kaya, S.; Bekdik, C. F. (Nuklearmedizin - NuclearMedicine, 1994)
Glutathione labelled with 99mTc was used to study blood clearance and normal distribution in 3 healthy volunteers and in 10 patients with biopsy-proven tumors in the head and neck region. Static scintigrams were obtained at 1, 3, 6, and 24 h. ROIs over tumors and normal soft tissues were compared to obtain T/N ratios. In normal subjects blood clearance reached a plateau at 6 h; no radioactivity accumulation in the head and neck region was observed. Only the cardiac blood pool, the liver, the kidneys and the urinary bladder were evident. Excretion was via the kidneys. Malignant tumors and metastases were well visualized in 7 patients (true-positive), starting at 1 h. The mean T/N ratio was 2.69 ± 0.77. The best images were obtained at 3-6 h. 1 false-positive (granula-matous reaction), 1 false-negative (malignant epithelial tumor in the radix of tongue) and 1 true-negative (angiofibroma) results were obtained. 99mTc-GSH is a potential radiopharmaceutical for the scintigraphic visualization of head and neck tumors. Further clinical studies are warranted to show its sensitivity and accuracy.
Keywords: 99mTc glutathione; head and neck tumors; blood clearance